A stable sodium metaaluminate solution and preparation method thereof

By adding modified hyaluronate and other stabilizers in the preparation process of sodium metaaluminate solution and carrying out pressure filtering and decolorization treatment, the problem of unstable sodium metaaluminate solution is solved, and efficient and stable preparation of sodium metaaluminate solution is achieved, reducing production costs and aluminum losses.

CN117416978BActive Publication Date: 2025-04-29JINLIWANG IND & TRADE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311566279.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-23
Publication Date
2025-04-29
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

The existing sodium metaaluminate solution is unstable during transportation and storage, and is prone to hydrolysis to form oxyaluminum colloid precipitation, affecting the use of equipment and catalyst efficiency.

Method used

By reacting aluminum hydroxide and sodium hydroxide with stabilizers such as modified hyaluronate, ethylenediamine cotton fiber, mannitol and maleic anhydride styrene copolymer under specific conditions, a stable sodium metaaluminate solution was prepared and filtered and decolorized by a filter press to obtain a high concentration and stable sodium metaaluminate solution.

Benefits of technology

The stability of sodium metaaluminate solution is achieved, the precipitation formation is reduced, the service life of the solution is extended, the production cost is reduced, and the efficiency of aluminum recycling is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117416978B_ABST
    Figure CN117416978B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum chemical industry, and discloses a stable sodium aluminate solution and a preparation method thereof. Aluminum hydroxide, sodium hydroxide and a stabilizer are added to molten corundum slag discharged during ferrovanadium smelting to obtain a stable sodium aluminate solution. The obtained sodium aluminate is filtered by a filter press, and the residue after the filtering is taken out and mixed with raw materials. After the steps, the residue is discarded. The prepared stable sodium aluminate enables aluminum recycling, reduces losses, greatly reduces production costs, simplifies processes, saves equipment, and improves storage and transportation time after adding a stabilizer. The invention has broad application prospects in the fields of sewage treatment, catalysts, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum chemical industry, in particular to a stable sodium metaaluminate solution and a preparation method thereof. Background Art

[0002] Sodium aluminate is an alkaline substance, a white particle, hygroscopic, very soluble in water, insoluble in ethanol, and its aqueous solution is strongly alkaline. It is widely used in civil engineering. This product is mixed with water glass for plugging leaks in construction. It is a good filler when mixed with aluminum sulfate in the papermaking industry. It is used as a water purifier in sewage treatment and as a filler for cement. It is also used in the fields of pharmaceuticals, petrochemicals, printing and dyeing, textiles, catalysts, etc. Thermodynamics of sodium aluminate solution is unstable. During transportation and storage, the solution hydrolyzes to form colloidal aluminum oxide precipitation. The precipitation generated by the hydrolysis of sodium aluminate solution will accumulate on the inner wall of transportation equipment, transport vehicles, and pipelines, which will affect the use of equipment and cause product loss. Sodium aluminate itself will also undergo structural changes. In many current chemical productions, a large amount of activated alumina is required as a catalyst, requiring alumina to have high activity, high purity, high specific surface area, and high pore volume. Since general γ-Al2O3 contains a large amount of harmful impurities, such as sodium, silicon, iron and calcium ions, which can poison the catalyst and reduce the catalytic efficiency, in order to avoid catalyst poisoning, many catalyst fields use ultra-high activity alumina, and its precursor is mostly ultra-high purity pseudo-boehmite. For example, patent number CN1401577A reports a method for preparing sodium aluminate solution using diaspore, which reduces the amount of sodium aluminate solution carried away by the slag, but the obtained sodium aluminate solution is unstable and easy to form precipitation. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the deficiencies in the prior art, the present invention provides a stable sodium aluminate solution and a preparation method thereof.

[0005] (II) Technical solution

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a stable sodium aluminate solution, the method comprising the following steps:

[0007] (1) Add sodium hydroxide solution and deionized water into a reactor, start stirring at a speed of 100-110 r / min, raise the temperature to 90-100°C, then add aluminum hydroxide and sodium hydroxide solid, maintain the temperature at 80-100°C and stir thoroughly until the aluminum hydroxide is completely dissolved. After 1-2 hours, add water-quenched corundum slag and stabilizer in sequence, and stir evenly at 30-40 r / min to obtain sodium aluminate;

[0008] (2) The obtained sodium aluminate is filtered by a filter press at a temperature of 50-60° C., the product is decolorized to obtain a stable sodium aluminate solution, the residue after the filtration is taken out and mixed with the raw material, and the residue is discarded after the above steps.

[0009] Preferably, the stabilizer in (1) is composed of 10-12 parts by weight of modified hyaluronate, 15-20 parts by weight of ethylenediamine cotton fiber, 8-14 parts by weight of mannitol, and 20-30 parts by weight of maleic anhydride styrene copolymer.

[0010] Preferably, the sodium hydroxide solution in step (1) accounts for 50-70% of the total sodium hydroxide reaction feed; the mass ratio of the aluminum hydroxide powder to the total sodium hydroxide feed is 1.1-1.2.

[0011] Preferably, the preparation method of the modified hyaluronate is: react hyaluronic acid with a 30-40% by mass sodium hydroxide solution at 70-90°C for 1-2h, and add epichlorohydrin and N,N-dimethylformamide thereto, the reaction time is 1-2h, the reaction temperature is 90-100°C, and then diethylenetriethylamine is added to react at 90-110°C for 3-5h to obtain a crude product, the crude product is washed with distilled water, vacuum pumped and filtered, and dried to obtain the modified hyaluronate.

[0012] Preferably, the mass ratio of the hyaluronic acid, epichlorohydrin, N,N-dimethylformamide and diethylenetriethylamine is 1:3.54-5.90:3.58-5.7:2.18-3.27.

[0013] Preferably, the preparation method of the water-quenched corundum slag is: water quenching the molten corundum slag discharged during the ferrovanadium smelting process, and then drying and crushing it to obtain water-quenched corundum slag, wherein the corundum slag is the corundum slag produced during the preparation of ferrovanadium alloy by aluminothermic reduction, the particle size of the corundum slag is 80-180 mesh, and the smelting temperature is 1200-1500°C.

[0014] Preferably, the stabilizer is added in an amount of 1.5-3wt%.

[0015] Preferably, the stable sodium aluminate solution comprises the following components: a stabilizer and a sodium aluminate solution, wherein the molecular formula of sodium aluminate is Na[Al(OH)4].

[0016] 3. Beneficial technical effects

[0017] The present invention collects molten corundum slag discharged during the ferrovanadium smelting process, adds aluminum hydroxide, sodium hydroxide and a stabilizer to the molten corundum slag to obtain a stable sodium aluminate solution, filters the obtained sodium aluminate with a filter press, takes out the residue after the filtration and mixes it with a raw material, and discards the residue after the steps, so that aluminum recycling reduces losses and greatly reduces production costs, simplifies the process, saves equipment, and efficiently utilizes the corundum slag to make the sodium aluminate solution higher in concentration. The shared electron pairs of modified sodium hyaluronate and ethylenediamine cotton fiber or mannitol or lysine anhydride styrene copolymer can be combined with aluminate to form a chelate, and the chelate adsorbs the ions of the sodium aluminate solution, destroys the directional and orderly arrangement of the ions around the water molecules, and enters the chelate to make it more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a process flow chart for preparing a stable sodium aluminate solution;

[0019] Figure 2 It is the reaction circuit diagram of modified hyaluronic acid. DETAILED DESCRIPTION

[0020] Example 1

[0021] A method for preparing a stable sodium metaaluminate solution comprises the following steps:

[0022] (1) 135 g of sodium hydroxide solution and 220 g of deionized water were added to a reactor, stirring was started at a speed of 100 r / min, the temperature was raised to 90°C, 183.4 g of aluminum hydroxide and 65 g of sodium hydroxide solid were added thereto, the temperature was maintained at 80°C and stirred until the aluminum hydroxide was completely dissolved. After 1 hour, 100 g of water-quenched corundum slag and stabilizer were added in sequence, and the mixture was stirred at 30 r / min to obtain sodium aluminate;

[0023] (2) The obtained sodium aluminate is filtered by a filter press at a temperature of 50° C., the product is decolorized to obtain a stable sodium aluminate solution, the residue after the filtration is taken out and mixed with the raw material, and the residue is discarded after the above steps.

[0024] The stabilizer is composed of 10 parts of modified hyaluronate, 15 parts of ethylenediamine cotton fiber, 8 parts of mannitol and 20 parts of maleic anhydride styrene copolymer in parts by weight.

[0025] The preparation method of the modified hyaluronate is as follows: 2g of hyaluronic acid is reacted with a 30% by mass sodium hydroxide solution at 70°C for 1h, and 11.8g of epichlorohydrin and 11.4g of N,N-dimethylformamide are added thereto, the reaction time is 1h, the reaction temperature is 90°C, and then 6.54g of diethylenetriethylamine is added and reacted at 90°C for 3h to obtain a crude product, the crude product is washed with distilled water, filtered by a vacuum pump, and dried to obtain the modified hyaluronate.

[0026] The preparation method of the water-quenched corundum slag is as follows: molten corundum slag discharged during ferrovanadium smelting is water-quenched, then dried, and crushed to obtain water-quenched corundum slag, wherein the corundum slag is corundum slag produced during the preparation of ferrovanadium alloy by aluminothermic reduction, the particle size of the corundum slag is 80 mesh, and the smelting temperature is 1200°C.

[0027] Example 2

[0028] A method for preparing a stable sodium metaaluminate solution comprises the following steps:

[0029] (1) Add 140 g of sodium hydroxide solution and 250 g of deionized water into a reactor, start stirring at a speed of 110 r / min, raise the temperature to 100°C, then add 247.5 g of aluminum hydroxide and 130 g of sodium hydroxide solid, keep stirring at 100°C until the aluminum hydroxide is completely dissolved. After 2 hours, add 150 g of water-quenched corundum slag and stabilizer in sequence, and stir evenly at 40 r / min to obtain sodium aluminate;

[0030] (2) The obtained sodium aluminate is filtered by a filter press at a temperature of 60° C., the product is decolorized to obtain a stable sodium aluminate solution, the residue after the filtration is taken out and mixed with the raw material, and the residue is discarded after the above steps.

[0031] The weight proportions of the stabilizer are 12 parts of modified hyaluronate, 20 parts of ethylenediamine cotton fiber, 14 parts of mannitol, and 30 parts of maleic anhydride styrene copolymer.

[0032] The preparation method of the modified hyaluronate is as follows: 4g of hyaluronic acid is reacted with a 40% by mass sodium hydroxide solution at 90°C for 2h, and 14.6g of epichlorohydrin and 11.4g of N,N-dimethylformamide are added thereto, the reaction time is 1h, the reaction temperature is 90°C, and then 6.54g of diethylenetriethylamine is added and reacted at 90°C for 3h to obtain a crude product, the crude product is washed with distilled water, filtered by a vacuum pump, and dried to obtain the modified hyaluronate.

[0033] The preparation method of the water-quenched corundum slag is as follows: molten corundum slag discharged during ferrovanadium smelting is water-quenched, then dried, and crushed to obtain water-quenched corundum slag, wherein the corundum slag is corundum slag produced during the preparation of ferrovanadium alloy by aluminothermic reduction, the particle size of the corundum slag is 180 mesh, and the smelting temperature is 1500°C.

[0034] Example 3

[0035] A method for preparing a stable sodium metaaluminate solution comprises the following steps:

[0036] (1) 137.5 g of sodium hydroxide solution and 235 g of deionized water were added to a reactor, stirring was started at a speed of 105 r / min, the temperature was raised to 95°C, and then 215.45 g of aluminum hydroxide and 97.5 g of sodium hydroxide solid were added thereto, and the temperature was kept at 90°C and stirred until the aluminum hydroxide was completely dissolved. After 1.5 h, 125 g of water-quenched corundum slag and stabilizer were added in sequence, and the mixture was stirred at 35 r / min to obtain sodium aluminate;

[0037] (2) The obtained sodium aluminate is filtered by a filter press at a temperature of 55° C., the product is decolorized to obtain a stable sodium aluminate solution, the residue after the filtration is taken out and mixed with the raw material, and the residue is discarded after the above steps.

[0038] The weight proportions of the stabilizer are 11 parts of modified hyaluronate, 17.5 parts of ethylenediamine cotton fiber, 11 parts of mannitol, and 25 parts of maleic anhydride styrene copolymer.

[0039] The preparation method of the modified hyaluronate is as follows: 3g of hyaluronic acid is reacted with a 35% by mass sodium hydroxide solution at 80°C for 1.5h, and 13.2g of epichlorohydrin and 12.85g of N,N-dimethylformamide are added thereto, the reaction time is 1.5h, the reaction temperature is 95°C, and then 7.63g of diethylenetriethylamine is added and reacted at 100°C for 4h to obtain a crude product, the crude product is washed with distilled water, filtered with a vacuum pump, and dried to obtain the modified hyaluronate.

[0040] The preparation method of the water-quenched corundum slag is as follows: molten corundum slag discharged during ferrovanadium smelting is water-quenched, then dried, and crushed to obtain water-quenched corundum slag, wherein the corundum slag is corundum slag produced during the preparation of ferrovanadium alloy by aluminothermic reduction, the particle size of the corundum slag is 130 mesh, and the smelting temperature is 1350°C.

[0041] Example 4

[0042] A method for preparing a stable sodium metaaluminate solution comprises the following steps:

[0043] (1) 137.5 g of sodium hydroxide solution and 235 g of deionized water were added to a reactor, stirring was started at a speed of 105 r / min, the temperature was raised to 95°C, and then 215.45 g of aluminum hydroxide and 97.5 g of sodium hydroxide solid were added thereto, and the temperature was kept at 90°C and stirred until the aluminum hydroxide was completely dissolved. After 1.5 h, 125 g of water-quenched corundum slag and stabilizer were added in sequence, and the mixture was stirred at 35 r / min to obtain sodium aluminate;

[0044] (2) The obtained sodium aluminate is filtered by a filter press at a temperature of 55° C., the product is decolorized to obtain a stable sodium aluminate solution, the residue after the filtration is taken out and mixed with the raw material, and the residue is discarded after the above steps.

[0045] The weight proportions of the stabilizer are 12 parts of modified hyaluronate, 20 parts of ethylenediamine cotton fiber, 14 parts of mannitol, and 30 parts of maleic anhydride styrene copolymer.

[0046] The preparation method of the modified hyaluronate is as follows: 4g of hyaluronic acid is reacted with a 40% by mass sodium hydroxide solution at 90°C for 2h, and 14.6g of epichlorohydrin and 11.4g of N,N-dimethylformamide are added thereto, the reaction time is 1h, the reaction temperature is 90°C, and then 6.54g of diethylenetriethylamine is added and reacted at 90°C for 3h to obtain a crude product, the crude product is washed with distilled water, filtered by a vacuum pump, and dried to obtain the modified hyaluronate.

[0047] The preparation method of the water-quenched corundum slag is as follows: molten corundum slag discharged during ferrovanadium smelting is water-quenched, then dried, and crushed to obtain water-quenched corundum slag, wherein the corundum slag is corundum slag produced during the preparation of ferrovanadium alloy by aluminothermic reduction, the particle size of the corundum slag is 80 mesh, and the smelting temperature is 1200°C.

[0048] Example 5

[0049] A method for preparing a stable sodium metaaluminate solution comprises the following steps:

[0050] (1) Add 140 g of sodium hydroxide solution and 250 g of deionized water into a reactor, start stirring at a speed of 110 r / min, raise the temperature to 100°C, then add 247.5 g of aluminum hydroxide and 130 g of sodium hydroxide solid, keep stirring at 100°C until the aluminum hydroxide is completely dissolved. After 2 hours, add 150 g of water-quenched corundum slag and stabilizer in sequence, and stir evenly at 40 r / min to obtain sodium aluminate;

[0051] (2) The obtained sodium aluminate is filtered by a filter press at a temperature of 60° C., the product is decolorized to obtain a stable sodium aluminate solution, the residue after the filtration is taken out and mixed with the raw material, and the residue is discarded after the above steps.

[0052] The weight proportions of the stabilizer are 11 parts of modified hyaluronate, 17.5 parts of ethylenediamine cotton fiber, 11 parts of mannitol, and 25 parts of maleic anhydride styrene copolymer.

[0053] The preparation method of the modified hyaluronate is as follows: 3g of hyaluronic acid is reacted with a 35% by mass sodium hydroxide solution at 80°C for 1.5h, and 13.2g of epichlorohydrin and 12.85g of N,N-dimethylformamide are added thereto, the reaction time is 1.5h, the reaction temperature is 95°C, and then 7.63g of diethylenetriethylamine is added and reacted at 100°C for 4h to obtain a crude product, the crude product is washed with distilled water, filtered with a vacuum pump, and dried to obtain the modified hyaluronate.

[0054] The preparation method of the water-quenched corundum slag is as follows: molten corundum slag discharged during ferrovanadium smelting is water-quenched, then dried, and crushed to obtain water-quenched corundum slag, wherein the corundum slag is corundum slag produced during the preparation of ferrovanadium alloy by aluminothermic reduction, the particle size of the corundum slag is 80 mesh, and the smelting temperature is 1200°C.

[0055] Comparative Example 1

[0056] A method for preparing a stable sodium metaaluminate solution comprises the following steps:

[0057] (1) 135 g of sodium hydroxide solution and 220 g of deionized water were added to a reactor, stirring was started at a speed of 100 r / min, the temperature was raised to 90°C, 183.4 g of aluminum hydroxide and 65 g of sodium hydroxide solid were added thereto, the temperature was maintained at 80°C and stirred until the aluminum hydroxide was completely dissolved. After 1 hour, 100 g of water-quenched corundum slag and stabilizer were added in sequence, and the mixture was stirred at 30 r / min to obtain sodium aluminate;

[0058] (2) The obtained sodium aluminate is filtered by a filter press at a temperature of 50° C., the product is decolorized to obtain a stable sodium aluminate solution, the residue after the filtration is taken out and mixed with the raw material, and the residue is discarded after the above steps.

[0059] The weight proportions of the stabilizer are 12 parts of modified hyaluronate, 20 parts of ethylenediamine cotton fiber, 14 parts of mannitol, and 30 parts of maleic anhydride styrene copolymer.

[0060] The preparation method of the modified hyaluronate is as follows: 4g of hyaluronic acid is reacted with a 40% by mass sodium hydroxide solution at 90°C for 2h, and 14.6g of epichlorohydrin and 11.4g of N,N-dimethylformamide are added thereto, the reaction time is 1h, the reaction temperature is 90°C, and then 6.54g of diethylenetriethylamine is added and reacted at 90°C for 3h to obtain a crude product, the crude product is washed with distilled water, filtered by a vacuum pump, and dried to obtain the modified hyaluronate.

[0061] The preparation method of the water-quenched corundum slag is as follows: molten corundum slag discharged during ferrovanadium smelting is water-quenched, then dried, and crushed to obtain water-quenched corundum slag, wherein the corundum slag is corundum slag produced during the preparation of ferrovanadium alloy by aluminothermic reduction, the particle size of the corundum slag is 130 mesh, and the smelting temperature is 1350°C.

[0062] As can be seen from the above table, Example 3 of the stable sodium aluminate solution of the present invention has the best effect, good stability and long maintenance time.

[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a stable sodium aluminate solution, characterized in that: The method comprises the following steps: (1) 137.5 g of sodium hydroxide solution and 235 g of deionized water were added to a reactor, stirring was started at a speed of 105 r / min, the temperature was raised to 95°C, and then 215.45 g of aluminum hydroxide and 97.5 g of sodium hydroxide solid were added thereto, and the temperature was kept at 90°C and stirred until the aluminum hydroxide was completely dissolved. After 1.5 h, 125 g of water-quenched corundum slag and stabilizer were added in sequence, and the mixture was stirred at 35 r / min to obtain sodium aluminate; (2) filtering the obtained sodium aluminate by a filter press at a temperature of 55° C., decolorizing the product to obtain a stable sodium aluminate solution and a residue, taking out the residue after the filtration, mixing it again with a sodium hydroxide solution and deionized water, and discarding the residue after the reaction in step (1), and reusing the stable sodium aluminate solution after the filtration; The stabilizer is calculated by weight as follows: 11 parts of modified hyaluronate, 17.5 parts of ethylenediamine cotton fiber, 11 parts of mannitol, and 25 parts of maleic anhydride styrene copolymer; The preparation method of the modified hyaluronate is as follows: 3g of hyaluronic acid is reacted with a 35% sodium hydroxide solution at 80°C for 1.5h, and 13.2g of epichlorohydrin and 12.85g of N,N-dimethylformamide are added thereto for 1.5h at a reaction temperature of 95°C, and then 7.63g of diethylenetriethylamine is added and reacted at 100°C for 4h to obtain a crude product, and the crude product is washed with distilled water, filtered by vacuum pump, and dried to obtain the modified hyaluronate; The preparation method of the water-quenched corundum slag is as follows: molten corundum slag discharged during ferrovanadium smelting is water-quenched, then dried, and crushed to obtain water-quenched corundum slag, wherein the corundum slag is the corundum slag produced during the preparation of ferrovanadium alloy by aluminothermic reduction, the particle size of the corundum slag is 130 mesh, and the smelting temperature is 1350°C.

Citation Information

Patent Citations

  • Method for preparing sodium metaaluminate solution for synthesis of zeolite with diasporite

    CN1401577A

  • Method for preparing sodium metaaluminate from corundum slag

    CN103408049A

  • Preparation method of sodium metaaluminate solution

    CN103466670A